Oxygenated bottom water conditions on Broken Ridge (central Indian Ocean) in the last 9 million years - Lyu, Jing; Barragán-Montilla, Sofía; Auer, Gerald; Bialik, Or M.; Del Gaudio, Arianna V.; Sarr, Anta-Clarisse; De Vleeschouwer, David (Frontiers in Earth Science, 2025)
The Late Miocene and Early Pliocene were characterized by widespread oxygen depletion in the Pacific and Indian Oceans, coinciding with the “Late Miocene–Early Pliocene Biogenic Bloom” (LMBB). In the Indian Ocean, this oxygen depletion has been linked to enhanced productivity in the northern basins, leading to Oxygen Minimum Zone (OMZ) expansion. A longstanding hypothesis proposes that the OMZ extended south of Broken Ridge (∼31°S). We test this hypothesis using benthic foraminiferal assemblages from ODP Site 752 (∼1086 m water depth) spanning the last 9 Myr. We apply a semi-quantitative reconstruction of bottom water oxygenation using the Enhanced Benthic Foraminiferal Oxygen Index (EBFOI), benchmarked against the present-day core-top assemblage. Our results indicate persistently oxic bottom water conditions (3.2–5.2 mL/L) throughout the study interval. Although significant faunal changes occur, particularly between 5.5 and 2.2 Ma, these do not align with LMBB timing. Instead, we interpret assemblage shifts as responses to the intensification of Tasman Leakage, which brought oxygen-rich intermediate waters into the southern Indian Ocean. Our results challenge previous interpretations of OMZ expansion to Broken Ridge and highlight the role of southward water mass sourcing in shaping intermediate-depth oxygenation. This study provides a new mechanistic framework and emphasizes the importance of integrating faunal, sedimentological, and geochemical data to reassess regional OMZ histories.